THE ADAPTATION CHARACTERISTICS OF THE MOVEMENT ANALYZER ARE INFLUENCED BY PHYSICAL EXERCISE. - Yoldasheva Roila Jumaevna; Fayziyeva Kibriyo Tuvlanovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The movement analyzer, commonly referred to as the neuromuscular or motor analyzer, plays a crucial role in regulating posture, coordinating movement patterns, and ensuring the accuracy of motor actions. Physical exercise has a strong influence on the functional and adaptive characteristics of this system. The adaptive responses include improved proprioceptive sensitivity, enhanced neuromuscular coordination, optimized muscle recruitment patterns, and increased efficiency in central nervous system (CNS) regulation. This article discusses the structural and functional components of the movement analyzer, the physiological mechanisms of adaptation during physical exercise, and the long-term effects of training on motor control. Special emphasis is placed on the neuroplastic changes that occur in response to regular training loads and the factors determining the stability and efficiency of adaptive responses.